2009
DOI: 10.4049/jimmunol.0803023
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Osteopontin Modulates Chronic Restraint Stress-Induced Thymus Atrophy by Regulating Stress Hormones: Inhibition by an Anti-Osteopontin Monoclonal Antibody

Abstract: Osteopontin (OPN) is a cytokine implicated in mediating responses to certain stressors, including mechanical, oxidative, and cellular stress. However, the involvement of OPN in responding to other physical and psychological stress is largely unexplored. Our previous research revealed that OPN is critical for hind limb-unloading induced lymphoid organ atrophy through modulation of corticosteroid production. In this study, we demonstrate that OPN−/− mice are resistant to chronic restraint stress (CRS)-induced ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…May this be, not because OPN is essential for scoliosis pathogenesis, but because OPN deficiency reduces stress reactions in mice [260]?…”
Section: Scientific Basis Of Leptin-hypothalamic-sympathetic Nervous mentioning
confidence: 99%
See 1 more Smart Citation
“…May this be, not because OPN is essential for scoliosis pathogenesis, but because OPN deficiency reduces stress reactions in mice [260]?…”
Section: Scientific Basis Of Leptin-hypothalamic-sympathetic Nervous mentioning
confidence: 99%
“…For, in mice, circulating OPN plays a significant role in the body's reaction to stress by regulating hormones of the hypothalamic-pituitary-adrenal axis (HPA) [260] modulated by leptin which activates the JAK/STAT pathway. Stressors cause less up-regulation of the stress hormone corticosterone in OPN-deficient mice [260].…”
Section: Scientific Basis Of Leptin-hypothalamic-sympathetic Nervous mentioning
confidence: 99%
“…It has been shown that chronic stress-induced alterations of immune responses could result from increased cell death and apoptosis or decreased cell proliferation [4,5,14]. Physical or psychological stress promotes stress hormone and neuronal transmitters [15,32,33]. However, the role of TLR9 in stress-mediated immune responses has remained unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms by which TLR9 participate in chronic stress-induced immune suppression are unexplored. To define the role of immune responses and stress hormones in mice, chronic restraint stress murine model has been widely employed [5,15]. We utilized this model to investigate TLR9-mediated immune responses as evaluated by alterations in the number of apoptosis, corticosterone production, and the balance of Th1 and Th2 cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…The relevance in thymic atrophy of increased corticosteroid levels which directly induce apoptosis in developing thymocytes is well documented [34,35,36]. Recently, it was described that glucocorticoids affect the thymic epithelial network, reducing the expression of the transcription factor FoxN1 and its regulator Wnt-4 [37].…”
Section: Discussionmentioning
confidence: 99%